2004
DOI: 10.1111/j.1399-3011.2004.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and lytic activity of eumenine mastoparan: a new antimicrobial peptide from wasp venom

Abstract: Eumenine mastoparan-AF (EMP-AF) is a novel membrane active tetradecapeptide recently isolated from the venom of solitary wasp, Anterhynchium flavomarginatum micado. It was reported previously that EMP-AF peptide presented low cytolytic activities in human erythrocytes and in RBL-2H3 mast cells. In the present work, we observed that this peptide is able to permeate anionic liposomes, and in less extension also the neutral ones. We present evidences showing that the permeation ability is well correlated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 38 publications
1
39
0
2
Order By: Relevance
“…It has been established that at a given MLT concentration after the formation process the pores are stable (Ladokhin et al 1997;Yang et al 2001;Naito et al 2000;Chen et al 2003;dos Santos Cabrera et al 2004;Huang et al 2004;Allende et al 2005;Macháň et al 2010); however, in our previous work with single giant vesicles, we investigated the interactions between the vesicles and MLT, and showed that in a wide range of MLT concentrations the MLT-induced membrane permeability is increasing with MLT concentration and also with time at a given concentration (Mally et al 2007). Namely, the osmotically tensed vesicles underwent a series of bursts, with vesicle membrane resealing after each burst.…”
Section: Introductionmentioning
confidence: 95%
“…It has been established that at a given MLT concentration after the formation process the pores are stable (Ladokhin et al 1997;Yang et al 2001;Naito et al 2000;Chen et al 2003;dos Santos Cabrera et al 2004;Huang et al 2004;Allende et al 2005;Macháň et al 2010); however, in our previous work with single giant vesicles, we investigated the interactions between the vesicles and MLT, and showed that in a wide range of MLT concentrations the MLT-induced membrane permeability is increasing with MLT concentration and also with time at a given concentration (Mally et al 2007). Namely, the osmotically tensed vesicles underwent a series of bursts, with vesicle membrane resealing after each burst.…”
Section: Introductionmentioning
confidence: 95%
“…The hydrophobic nature of most of the amino acid residues in mastoparans usually leads them to adopt amphipathic α-helical conformations in micellar solvents [5] and in a membrane-bound state [6]. The cationicity of mastoparans contributes to the formation of discriminate anionic vesicles, which favor their antimicrobial activity [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It was previously reported that the deamidation of the C-terminus of the membrane-active peptide EMP-AF1 reduces its antimicrobial potency [5], while suppressing its hemolytic activity [14].…”
Section: Introductionmentioning
confidence: 99%
“…Mastoparan has been shown to take the ␣-helical conformation upon binding with phospholipid membrane (37) and to cause liposome permeabilization in a transmembrane potential-dependent manner (36) that seems to be the mechanism for mitochondria as well (38). Recently, it has been shown that the liposome permeation ability of eumenine mastoparan, a novel natural tetradecapeptide with a broad-spectrum inhibitory activity against Gram-positive and Gram-negative bacteria, is correlated with the amount of helical conformation in the membrane (39).…”
mentioning
confidence: 99%